Program Evaluation in the Context of Supervision Regime Change: Motivational Interviewing in Colorado. (29th July 2018) - Lin, Jeffrey
Abstract : This study assesses the effectiveness of an evidence-based counseling strategy employed by Colorado parole officers called Motivational Interviewing (MI), which aims to reduce parolee recidivism. I employ a quasi-experimental research design in which the caseloads of MI-trained officers are divided into two sub-samples: parolees supervised before the achievement of MI certification and parolees supervised after certification. Regression analyses show that MI is associated with recidivism reduction, but this relationship would not have been revealed without accounting for a high-profile crime that interrupted the study period—the murder of the Executive Director of the Colorado Department of Corrections by a high-risk parolee that had absconded from supervision. This crime caused a public relations crisis for the parole agency, which responded by lowering tolerance for misconduct. This reduction in tolerance increased recidivism rates among parolees in Colorado, obscuring the effect of MI on parole outcomes. Theoretical and policy implications are discussed.